2022
DOI: 10.1016/j.pnpbp.2021.110507
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates and predictors of the antidepressant response to repeated ketamine infusions in treatment-resistant depression

Abstract: Traditional antidepressants, which act on the serotonin, dopamine, and norepinephrine systems, require many weeks to produce a therapeutic effect and are not effective for every patient. A sub-anesthetic dose of the anesthetic agent ketamine, a glutamate N-methyl-Daspartate receptor antagonist, has been shown to produce a rapid and robust antidepressant effect in treatment-resistant major depressive disorder (MDD). As depressive symptoms typically return after one week following a single infusion, recent work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 235 publications
2
7
1
Order By: Relevance
“…First, as expected, repeated exposure to forced swimming increased immobility in rats that were conditioned with SAL in the CS+ (Figure 2B), which is in line with previous studies that employed a repeated swim stress design (Dal-Zotto et al, 2000; Melanson et al, 2021; Mul et al, 2016). Also anticipated was the significant difference between the KET 20 group and all other groups at induction (FSS 1 ), an observation that is consistent with clinical reports of sustained antidepressant activity by KET (de la Salle et al, 2022; Li et al, 2022; Phillips et al, 2019). Importantly, the increase in immobility was not observed in rodents that were exposed to the KET CS+ prior to the last swim (FSS 3 ; Figure 2B), and this occurred in groups conditioned with both KET doses.…”
Section: Discussionsupporting
confidence: 77%
“…First, as expected, repeated exposure to forced swimming increased immobility in rats that were conditioned with SAL in the CS+ (Figure 2B), which is in line with previous studies that employed a repeated swim stress design (Dal-Zotto et al, 2000; Melanson et al, 2021; Mul et al, 2016). Also anticipated was the significant difference between the KET 20 group and all other groups at induction (FSS 1 ), an observation that is consistent with clinical reports of sustained antidepressant activity by KET (de la Salle et al, 2022; Li et al, 2022; Phillips et al, 2019). Importantly, the increase in immobility was not observed in rodents that were exposed to the KET CS+ prior to the last swim (FSS 3 ; Figure 2B), and this occurred in groups conditioned with both KET doses.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have shown that ketamine has a rapid and efficient antidepressant effect [80]. A recent metaanalysis has shown that intravenous ketamine has a better antidepressant effect than nasal spray [81].…”
Section: Clinical Neurophysiology Studies Of the Visual Cortexmentioning
confidence: 99%
“…Electrophysiological findings have also demonstrated that ketamine increases the latency of MMN responses in healthy participants ( Umbricht et al, 2000 ; Kreitschmann-Andermahr et al, 2001 ), though its effect on amplitude is stronger than its effect on latency ( Rosburg and Kreitschmann-Andermahr, 2016 ). In the context of the MMN response, ketamine administration was found to reduce frontal MMN amplitudes immediately post-infusion and again at 2 h post-infusion in MDD patients; furthermore, immediate change in MMN amplitude predicted antidepressant response ( de la Salle, 2022 ). In contrast, other studies that used a roving auditory oddball task collected 3–4 h post-ketamine infusion in MDD patients found that ketamine administration increased MMN response, but only when all repetitions of the post-deviant tone were analyzed ( Sumner et al, 2020 ).…”
Section: Antidepressant Drugs and Predictive Processesmentioning
confidence: 99%